1997
DOI: 10.1901/jeab.1997.67-145
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Reinforcement Dynamics in Three‐link Chained Schedules

Abstract: In two experiments rats were trained on three-link concurrent-chains schedules of reinforcement. In Experiment 1, additional entries to one terminal link were added during one of the middle links to a baseline schedule that was otherwise equal for the two chains, and, depending on the condition, these additional terminal-link presentations ended either in food or in no food. When food occurred, preference was always in favor of the chain with the additional terminal-link presentations (which also entailed a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Despite this limitation, the results make a strong case that the effect of stimuli intervening between choice responses and their outcomes exert their effect on the rate of learning by providing an avenue of transmitting the value of the outcomes in a backwards direction to the values of the choice alternatives. Taken together with previous results (Williams, 1994(Williams, , 1997Williams, Ploog, & Bell, 1995), the present study supports the thesis that understanding the conditioned reinforcement properties of the intervening stimuli is critical to predicting when intervening stimuli will or will not facilitate learning.…”
Section: Discussionsupporting
confidence: 89%
“…Despite this limitation, the results make a strong case that the effect of stimuli intervening between choice responses and their outcomes exert their effect on the rate of learning by providing an avenue of transmitting the value of the outcomes in a backwards direction to the values of the choice alternatives. Taken together with previous results (Williams, 1994(Williams, , 1997Williams, Ploog, & Bell, 1995), the present study supports the thesis that understanding the conditioned reinforcement properties of the intervening stimuli is critical to predicting when intervening stimuli will or will not facilitate learning.…”
Section: Discussionsupporting
confidence: 89%
“…Many experimental and theoretical papers on conditioned reinforcement in pigeons and rats have been published since the early 1960s using some version of the concurrent chains procedure of Autor (1960Autor ( , 1969. These studies have demonstrated a number of functional relations between rate measures and have led to several closely related theoretical proposals such as a version of the matching law, incentive theory, delay-reduction theory, and hyperbolic value-addition (e.g., Fantino 1969a,b;Grace 1994;Herrnstein 1964;Killeen 1982;Killeen & Fantino 1990;Mazur 1997Mazur , 2001Williams 1988Williams , 1994Williams , 1997. Nevertheless, there is as yet no theoretical consensus on how best to describe choice between sources of conditioned reinforcement, and no one has proposed an integrated theoretical account of simple chain and concurrent chain schedules.…”
Section: Concurrent-chain Schedulesmentioning
confidence: 99%
“…To establish conditions under which an improvement in acquisition behavior could be seen easily, the baseline of repeated-acquisition behavior was degraded by manipulating the stimuli associated with the response sequence (chain vs. tandem stimuli) and increasing the value of the fixed ratio (FR) under the second-order FR schedule in order to produce ratio strain. The ''tandem-strained'' condition also served as a control for the conditioned reinforcing and discriminative stimulus properties of the stimuli in the ''chain-strained'' condition (Thompson, 1970;Williams, 1997). Both of these conditions maintained high error levels and produced slow within-session acquisition under control conditions.…”
mentioning
confidence: 99%